Design of Bronze‐Rich Dual‐Phasic TiO2 Embedded Amorphous Carbon Nanocomposites Derived from Ti‐Metal–Organic Frameworks for Improved Lithium‐Ion Storage. Issue 11 (20th September 2022) - Ahn, Cheol Hyoun; Yang, Won Seok; Kim, Jeong Jae; Kim, Jae Hyun; Cho, Hyung Koun
Abstract: Dual‐phasic (DP)‐TiO2 ‐based composites are considered attractive anode materials for high lithium‐ion storage because of the synergetic contribution from dual‐phases in lithium‐ion storage. However, a comprehensive investigation on more efficient architectures and platforms is necessary to develop lithium‐storage devices with high‐rate capability and long‐term stability. Herein, for the first time, a rationally designed bronze‐rich DP‐TiO2 ‐embedded amorphous carbon nanoarchitecture, denoted as DP‐TiO2 @C, from sacrificial Ti‐metal–organic frameworks (Ti‐MOFs) via a two‐step pyrolysis process is proposed. The bronze/anatase DP‐TiO2 @C nanocomposites are successfully synthesized using a unique pyrolysis process, which decomposes individually the metal clusters and organic linkers of Ti‐MOFs. DP‐TiO2 @C exhibits a significantly high density and even distribution of nanoparticles (<5 nm), enabling the formation of numerous heterointerfaces. Remarkably, the bronze‐rich DP‐TiO2 @C shows high specific capacities of 638 and 194 mAh g −1 at current densities of 0.1 and 5 A g −1, respectively, owing to the contribution of the synergetic interfacial structure. In addition, reversible specific capacities are observed at a high rate (5 A g −1 ) during 6000 cycles. Thus, this study presents a new approach for the synthesis of DP‐TiO2 @C nanocomposites from a sacrificial Ti‐MOF and provides insights into the efficient control of the volume ratio in DP‐TiO2 anode architecture. Abstract : Bronze‐rich dual‐phasic TiO2 embedded carbon nanoarchitecture derived from Ti‐metal‐organic frameworks (Ti‐MOFs) is designed, for the first time, to achieve rationally anode materials. Individual pyrolysis of metal‐clusters and organic‐linkers within Ti‐MOFs enable to design the efficient materials combination and allow dual‐phasic nanoparticles to well distribution in carbon frameworks. Ti‐MOFs derived synergetic bronze‐rich dual‐phasic TiO2 electrode provide a useful approach for improving the energy storages.